Job Satisfaction and Labor Fluctuation: A Case Study in the Logistics Sector in Serbia - Milan Andrejić; Milorad Kilibarda; Vukašin Pajić (Logistics, 2022)
Background: There is a growing need for logistics professionals in different positions and with different competencies. The key question is how to attract and retain a highly skilled workforce. The purpose of this research is to determine what factors and how they affect employee’s satisfaction and loyalty in the logistics sector in the Serbian market; Methods: The impact of company size, primary business activity and employee position on labor loyalty and fluctuation were examined. The research hypotheses were tested on the basis of data obtained from a web survey that included 270 respondents from different industrial sectors in the Serbian market. Linear regression was used for hypothesis testing; Results: The results showed, among other things, that salary and advancement possibility are the main motives for changing jobs. The importance of basic professional knowledge acquired at the faculty for employment and working in various companies was confirmed; Conclusions: There are no papers in the literature that investigate job satisfaction and employee turnover in the logistics market. The results of this research, on the one hand, provide useful and accurate information for decision-making in order to improve the situation in the observed market, while on the other hand, provide an excellent basis for future research.